EVALUASI SISTEM PENDAFTARAN ONLINE PASIEN RAWAT JALAN MENGGUNAKAN METODE PIECES DI RUMAH SAKIT BAPTIS KEDIRI - Rince I.K, Klementina; Rachman, Mohammad Arief; Anggraeni, Femy (JRMIK, 2025)
Baptist Hospital Kediri has implemented an online outpatient registration system to increase the efficiency and effectiveness of health services. This research aims to evaluate the online registration system using the PIECES (Performance, Information, Economic, Control, Efficiency, and Service) method.This research uses descriptive qualitative methods with data collection techniques through interviews, observation and documentation studies.The results of the research show that the online registration system for outpatients at Baptis Kediri Hospital, from the performance aspect, the online registration system is stable so that the registration process runs smoothly, the information aspect of the online registration system is the quality of the information presentedis accurate and up to date, the economic aspect is cost implementation and maintenance of the system is very affordable so that it provides convenience for patients, internal and external control aspects have been maintained safely, the hospital has prepared a safe place for storing patient data both in the IT room and outside the hospital, the efficiency aspect of the online registration system is very efficient in saves time, costs and patients can register whenever and wherever the patient is without conventional registration, and the service aspect of the quality ofthe online registration service is very optimal, the service approach is very easy and can be done.Based on the research results, it can be concluded that the online outpatient registration system at Baptis Kediri Hospital in terms of service is very optimal, the system performance is very good, the quality of the informatin is up to date and accurate, the costs are cheap and easy to reach, internal and external controls arewell maintained . good and safe, and the quality of the online registration service is very fast and precise.